ART THERAPY FOR HARMONIZING DESIRE AND LIFE IN KOREAN SOCIETY - Lee, Soo-Jin (Journal of Dharma, 2021)
The purpose of this study is to diagnose and find solutions through art, based on a psychoanalytic perspective, seeing the increasing misery of Koreans as a signal to the frustration of desire and social incongruity. However, mental disorders have a double effect. Especially, anxiety has its fair share of negative repercussions such as fear, powerlessness, and sadness; it also enables inner inspection and acts as a signal of existence that can re-establish desire. Through a case study, this paper argues that art therapy can not only help individuals to understand their existence, but also restore intersubjective relationships and go toward sustainable society. This is because art is ultimately an act of practice aiming at the gaze, an indicator of existence. In the end, the central goal of humanity and social development should be to make them coexist in an ethical horizon through the restoration of the "original life."